Addiction and Liver Disease (Medicine Today, 2014)
Drug induced liver disease is a global problem. The aims of the study are to know the recreational drugs causing harmful effect on liver, epidemiology of addiction; pathophysiology and their consequences. The major findings published to date concerning different agents causing addiction and liver disease, their implications with regard to understanding disease mechanisms and their amplitude or spectrum are described. Addiction not only invites lot of sufferings to the family and the country, but also responsible for different types of liver disease including fatty liver, hepatitis and liver failure; responsible for mortality and morbidity. Among the addiction causing substances alcohol playing the main role for liver disease worldwide. Indirect effects of addiction on liver are hepatitis B, hepatitis C and their complication, mainly due to contamination of sharing needle. Majority of people in Bangladesh are life long abstainer. Excessive alcohol beverages and other substances like heroin, amphetamine are not harmless, rather they can cause serious liver diseases. There are some differences in prevalence of addiction and liver diseases among countries. Intravenous drug users are affected both directly and indirectly due to contaminated needle sharing . DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17926 Medicine Today 2013 Vol.25(2): 75-83